Python based event management analytics system (part A) - Ng, Han Sen (Nanyang Technological University, 2022)
A social network is a group of people (or organisations or other social entities) linked by social interactions such as friendship, co-working, or information sharing. Social Network Analysis (SNA) is the process of investigating social structures using networks and graph theory. SNA studies patterns of relationships among people, companies, states, and other social entities. It characterises network structures in terms of nodes (individual actors, people, or things within the network) and the ties, edges, or links (relationships or interactions) that connect them. The visual and statistical examination of human relationships is provided by social network analysis. In this paper, we explore the use of Python to perform Social Network Analysis in our use case; to understand the interactions and relationships of participants who have attended Nanyang Technological University (NTU) open-house events.